Representations of Experimentation in Contemporary Arabic Theatre: The Case of Sayyed Hafez - Abdulsattar AbdThabet (Basrah Arts Journal, 2024)
Art is a dynamic and renewing aesthetic vision. Since the dawn of creativity, arts have sought to break away from tradition and embrace new forms and elements in response to intellectual and other changes. Theatre, in particular, has experimented with its structure and content due to its inherent flexibility and transformative nature. Social and environmental conditions in the Arab world have driven theatre practitioners towards innovation. Many Arab playwrights responded to the events of 1967 by adopting an experimental approach in theatre. Egyptian playwright Sayyed Hafez is a key figure who emerged in the 1970s, contributing significantly to the renewal of theatrical composition. Realizing that traditional theatre was no longer effective in engaging society, Hafez introduced innovative ideas. Until the early 1970s, Arab and Egyptian theatre was predominantly traditional. However, new efforts to revitalize it began with Hafez’s experimental play "The Pride of Triviality in the Land of Meaninglessness," which broke classical norms and offered new perspectives on characters, settings, and heroism. Hafez continued his experimental approach in subsequent plays, such as "It Happened as It Happened but No Event Happened," "Silent Drums in the Blue Valleys," and "They Are as They Are but Not the Vagabonds." These works reflect his desire for rebellion and passion for experimentation in theatrical writing. This study aims to analyze the features of experimentation in Sayyed Hafez’s theatrical texts and their impact on the construction of the theatrical text. The significance of the research lies in exploring these experimental tendencies, benefiting specialists in theatrical criticism. The objective is to identify representations of experimentation in Hafez’s plays.